Formation, Contraction, and Mechanotransduction of Myofribrils in Cardiac Development: Clues from Genetics - Javier T. Granados-Riveron; J. David Brook (Biochemistry Research International)
Congenital heart disease (CHD) is the most common birth defect in humans. It is a leading infant mortality factor worldwide, caused by defective cardiac development. Mutations in transcription factors, signalling and structural molecules have been shown to contribute to the genetic component of CHD. Recently, mutations in genes encoding myofibrillar proteins expressed in the embryonic heart have also emerged as an important genetic causative factor of the disease, which implies that the contraction of the early heart primordium contributes to its morphogenesis. This notion is supported by increasing evidence suggesting that not only contraction but also formation, mechanosensing, and mechanotransduction of the cardiac myofibrillar proteins influence heart development. In this paper, we summarize the genetic clues supporting this idea.